Non‐Chromatographic Purification of Synthetic RNA Using Bio‐Orthogonal Chemistry. Issue 9 (27th September 2021) - He, Muhan; Wu, Xunshen; Mao, Song; Haruehanroengra, Phensinee; Khan, Irfan; Sheng, Jia; Royzen, Maksim
Abstract: Solid‐phase synthesis of RNA oligonucleotides over 100 nt in length remains challenging due to the complexity of purification of the target strands from the failure sequences. This article describes a non‐chromatographic procedure that will enable routine solid‐phase synthesis and purification of long RNA strands. The optimized five‐step process is based on bio‐orthogonal inverse electron demand Diels‐Alder chemistry between trans ‐cyclooctene (TCO) and tetrazine (Tz), and entails solid‐phase synthesis of RNA on a photo‐labile support. The target oligonucleotide strands are selectively tagged with Tz while on‐support. After photocleavage from the solid support, the target oligonucleotide strands can be captured and purified from the failure sequences using immobilized TCO. The approach can be applied for purification of 76‐nt long tRNA and 101‐nt long sgRNA for CRISPR experiments. Purity of the isolated oligonucleotides should be evaluated using gel electrophoresis, while functional fidelity of the sgRNA should be confirmed using CRISPR‐Cas9 experiments. © 2021 Wiley Periodicals LLC. Basic Protocol : Five‐step non‐chromatographic purification of synthetic RNA oligonucleotides Support Protocol 1 : Synthesis of the components that are required for the non‐chromatographic purification of long RNA oligonucleotides. Support Protocol 2 : Solid‐phase RNA synthesis